Editorial - Evangelista, Laura; Fonzo, Concetta (Community Notebook. People, Education and Welfare in the Society 5.0, 2025)
Evaluation is currently the focus of renewed attention, involving crucial areas such as education, welfare, social planning and research. In a context characterised by the growing complexity of social phenomena, there is a strong need for tools that are capable not only of measuring but also of guiding change. In this scenario, evaluation is a living and dynamic practice, capable of generating learning and transformation.This thematic issue of Quaderni di Comunità, entitled “The Challenges and Opportunities of Evaluation: From Theory to Practice”, invites us to rethink evaluation as a strategic lever for innovating educational, social and institutional processes. Through theoretical contributions, field experiences and evaluation practices, it explores the transformative potential of evaluation, which, from a simple control tool, evolves into a participatory process capable of reading contexts, giving voice to actors, restoring meaning to policies and guiding decisions.